(untitled) (Al-Qamar, 2022)
Atheism is a major challenge of 21st century for the believers of all religions. An atheist denies God’s commandments. Atheists present scientific logics to reject religion thoughts. The actual problem faced by a religion follower is that atheists demand worldly, materialistic, scientific, mechanical and intellectual reasoning about God & universe. To face such a challenge, the preachers of religion should have a great command about teachings of all religion on spiritual as well as natural bases. To deal a disbeliever one should practise a great tolerance. Even in the world of science and technology, man cannot deny God or religion. The success of eternal life based on his true belief. It’s the duty of representatives & preachers of a religion to preach positive and simple codes of life. So that complications of minds can be removed and save humanity from edge of chaos. A Muslim thinker Mr. Wahid-u-Din presents such scientific and mechanical reasoning of religion & universe.